Dinars and Dirhams
1 online resource.
Keywords: The present volume is dedicated to Michael L. Bates, Curator Emeritus of Islamic Coins at the American Numismatic Society. For more than forty years, Michael has been a major figure in the field of Islamic numismatics through his writing, teaching, and being a resource for scholars, students and collectors. The list of contributors to this volume and the range of their contributions are testament to Michael's continued and vital influence on numismatic and historical studies. This volume was previously published by the Jordan Center for Persian Studies, University of California - Irvine.